International Symposium held in Danang on 22-23 March 1990 - International Symposium on the Ancient Town of Hoi An (Ha Noi, 1991)
Contents:communique of the National commitee for the International Symposium on the Ancient Town of Hoi An
Keywords: Hội An (Vietnam),Hoi An (Vietnam); Lịch sử,History